Competitiveness In Entrepreneurs Refilling Mineral Water and Pulse Agent Payment Point Online Bank (PPOB) - Nia kurniah (JOURNAL OF SHARIA ECONOMICS, 2023)
The development of the visionary world of business in Indonesia is expanding. This can be seen from the emergence of many entrepreneurs, both in traditional and online stores. Clothing, food and other necessities for daily life are among the items available. In the world of entrepreneurship, competition or competitiveness cannot be avoided. Entrepreneurs are forced to compete to create something that can increase the added value of their products as a result of free trade. Claimed item benefits can strengthen the strength of other competitor items. An entrepreneur will always find new ways to improve and maintain the quality of his products in order to create new products